Akibat Hukum Bagi Anak Hasil Perkawinan Kewarganegaraan Campuran Yang Tidak Dicatatkan - Dini Mulia Mutmainah; Nikolas Andika S; Delfika Intania Rosadi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The law that applies to mixed nationality marriages can be seen based on the principles of Indonesian International Civil Law, including the principle of lex loci celebrationis, nationality or joint residence, where the marriage is held, where the husband and wife become citizens after marriage or where the husband and wife live. However, mixed marriages that are not recorded according to applicable regulations do not deprive children of their inheritance rights, especially from their fathers as long as there is recognition with an authentic deed. The fact that the marriage is not recorded does not mean that the marriage is void, but only that it has not been recognized so that the inheritance rights of the children are not obtained properly. Decision.of.the.Constitutional.Court.No.46/PUU-VIII/2010 is the latest legal breakthrough in which children outside the marriage of an unregistered marriage still have civil rights from both parents.